The Paradox of Unilateralism: Institutionalizing Failure In U.S.-Mexican Drug Strategies - Simon Reich; Mark Aspinwall (Norteamérica)
Realism posits that strong states use compulsory power to influence the behavior of weaker ones. If true, then U.S. policy toward Mexico on a key national security issue such as drugs should illustrate that claim and policy outcomes should reflect U.S. preferences. Yet, in exploring a series of bilateral case studies, this article suggests that unilateral U.S. government initiatives do not achieve their specified goals. Rather, we argue that Mexico effectively employs a series of “strangulation strategies.” These derail U.S. initiatives and –under specific conditions– result in institutional agreements that proscribe certain forms of behavior and reduce future U.S. autonomy.